Kesesuaian Karakteristik Kawasan Simpul Perpindahan Moda Transportasi Berbasis Transit Oriented Developmet (TOD) di Kawasan Transit Terminal Batu Ampar - Fearnisya, Salva; Hidayat, Arief; Nugroho, Rizky Arif; Depari, Andi Sahputra (COMPACT: Spatial Development Journal, 2024)
The population growth of Balikpapan city is influenced by in-migration. The population growth of Balikpapan City certainly has a big impact on the movement system in Balikpapan City. Balikpapan City has a high economic growth rate, which can be seen from the increase in investment and infrastructure development from year to year, thus encouraging an increase in the travel of people and goods using transportation facilities. In addition, the development and changes in land use functions that affect the generation, attraction and movement system as well as traffic characteristics of Balikpapan City. Based on this, in planning the transportation system of Balikpapan City, a transportation development plan is needed using the TOD Concept which has the function of utilizing dense mixed space with moderate to high space utilization intensity to reduce uneven distribution of population, prevent problems transportation in the form of congestion, and maintaining the availability of land in Balikpapan City, especially Batu Ampar Terminal and to find out the Development Potential of TOD-based transportation mode transfer node areas (Case Study: Batu Ampar Terminal). The goal is achieved by fulfilling 3 stages. First, analyze the characteristics of the Balikpapan city mode transfer node descriptively. Second, analysis of the pairing between the characteristics of the existing condition of the Batu Ampar terminal with the TOD Standard BPN ATR Regulation No. 16 of 2017. Finally, analyze the results of targets one and two to obtain a scenario for the development of TOD-based transportation mode transfer node areas in the Batu Ampar Terminal Transit Area. Keyboard : Transportation, Land Use, Transit Oriented Development